PENGARUH MINAT BELAJAR, GAYA BELAJAR, LINGKUNGAN BELAJAR, DAN DUKUNGAN ORANG TUA TERHADAP HASIL BELAJAR AKUNTANSI DI SMK NEGERI 1 KINALI TAHUN PELAJARAN 2024/2025 - Nauli, Syelin Oktavia; Sofyan, Erita; Stevani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the influence of learning interest, learning style, learning environment, and parental support on student accounting learning outcomes at SMK Negeri 1 Kinali for the 2024/2025 academic year. This research uses a quantitative approach with survey methods. The research population was all students of classes X and XI Accounting, totaling 95 people, with a sampling technique using total sampling. The research instrument is in the form of a questionnaire which has been tested for validity and reliability, while the data is analyzed using path analysis with the help of SPSS version 22. The research results show that learning interest, learning style, learning environment and parental support have a positive and significant effect on learning outcomes both partially and simultaneously. In particular, the variables of parental support and interest in learning provide the most dominant influence. These findings indicate that student learning success is not only influenced by internal factors such as motivation and learning style, but is also determined by external factors in the form of learning environment support and parental attention. Therefore, improving student learning outcomes requires the active involvement of all parties, including students, teachers, schools and families.